Prevalence of and Risk factors for Stunting among School Children and Adolescents in Abeokuta, Southwest Nigeria (Journal of Health, Population and Nutrition, 2011)
Stunting adversely affects the physical and mental outcome of children. The objectives of the study were to determine the prevalence of and risk factors associated with stunting among urban school children and adolescents in Abeokuta, Nigeria. Five hundred and seventy children aged 5-19 years were selected using the multi-stage random-sampling technique. Stunting was defined as height-for-age z-score (HAZ) of